2021
DOI: 10.1002/jca.21915
|View full text |Cite
|
Sign up to set email alerts
|

The first pediatric case of hemophagocytic lymphohistiocytosis secondary to Crimean‐Congo haemorrhagic fever successfully treated with therapeutic plasma exchange accompanying ribavirin and intravenous immunoglobulin

Abstract: Although Crimean‐Congo hemorrhagic fever (CCHF) is mild and self‐limited in children, some patients may develop excessive bleeding, massive liver necrosis, and multiple organ failure associated with secondary hemophagocytic lymphohistiocytosis (HLH) induced by cytokine storm. Treatment of CCHF is mainly symptomatic and supportive. The efficacy of ribavirin, which is the only antiviral drug in the treatment of CCHF, remains controversial. Although therapeutic plasma exchange (TPE) has been shown to beneficial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…One study reported HLH in 50% of adult CCHF patients ( 26 ); however, a case report describing an adult CCHF patient with HLH reported HLH as a rare condition ( 27 ). HLH is rarely reported among pediatric patients ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…One study reported HLH in 50% of adult CCHF patients ( 26 ); however, a case report describing an adult CCHF patient with HLH reported HLH as a rare condition ( 27 ). HLH is rarely reported among pediatric patients ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric cases of hemophagocytic lymphohistiocytosis (HLH) secondary to CCHF have been described ( 42 , 43 ). Secondary HLH, although rare, can be associated with malignancies, severe infections, medications, and autoimmune disorders and has been thought to be secondary to a hyperinflammatory syndrome ( 44 ).…”
Section: Clinical Featuresmentioning
confidence: 99%
“…The Crimean Congo hemorrhagic fever-associated HLH has been resolved using antiviral therapy combined with IVIG therapy and plasma exchange ( 91 ).…”
Section: Treatmentmentioning
confidence: 99%
“…Dengue virus plays a significant role in tropical countries (73,(83)(84)(85)(86)(87)(88)(89)(90). Tick-borne diseases include the Crimean-Congo hemorrhagic fever nairovirus (91,92) and the Eastern equine encephalitis virus (93). Sporadic case reports include HLH related to HAV (90,94), HBV (95), HIV (89,96), Adenovirus (72,89,97,98), Parvovirus B19 (72), Measles (88) and Influenza virus (99)(100)(101).…”
Section: Classificationmentioning
confidence: 99%